Synthesis and Characterization of Self-Assembled Porous Microspheres of Poly(o-chloroaniline) - Naveed Anjum, Muhammad; Mahmood Zia, Khalid; Zhu, Lihua; Nadeem Ahmad, Mirza; Farooq, Tahir; Zuber, Mohammad; Tang, Heqing (Asian Journal of Chemistry, 2015)
Self-assembled porous microspheres poly(o-chloroaniline) have been fabricated by simple oxidative polymerization of o-chloroaniline with camphor-sulfonic acid as dopant acid and ammonium persulfate as oxidant. In the synthesis system, formation of micelles of camphor-sulfonic acid in aqueous solution is a key factor in fabrication of porous microspheres of poly(o-chloroaniline). The conducting poly(o-chloroaniline) microspheres were characterized by means of Fourier transform infrared spectroscopy, UV-visible spectroscopy, X-ray diffraction and scanning electron microscopy. A mechanism has been proposed to explain the formation of poly(o-chloroaniline) microsphere which was supported by UV-visible spectroscopy and SEM data.